Comparing Cost-effectiveness of X-Stop With Minimally Invasive Decompression in Lumbar Spinal Stenosis. Issue 8 (15th April 2015) - Lønne, Greger; Johnsen, Lars Gunnar; Aas, Eline; Lydersen, Stian; Andresen, Hege; Rønning, Roar; Nygaard, Øystein P.
<x xml:space="preserve">Abstract</x> Study Design. Randomized clinical trial with 2-year follow-up. Objective. To compare the cost-effectiveness of X-stop to minimally invasive decompression in patients with symptomatic lumbar spinal stenosis. Summary of Background Data. Lumbar spinal stenosis is the most common indication for operative treatment in elderly. Although surgery is more costly than nonoperative treatment, health outcomes for more than 2 years were shown to be significantly better. Surgical treatment with minimally invasive decompression is widely used. X-stop is introduced as another minimally invasive technique showing good results compared with nonoperative treatment. Methods. We enrolled 96 patients aged 50 to 85 years, with symptoms of neurogenic intermittent claudication within 250-m walking distance and 1- or 2-level lumbar spinal stenosis, randomized to either minimally invasive decompression or X-stop. Quality-adjusted life-years were based on EuroQol EQ-5D. The hospital unit costs were estimated by means of the top-down approach. Each cost unit was converted into a monetary value by dividing the overall cost by the amount of cost units produced. The analysis of costs and health outcomes is presented by the incremental cost-effectiveness ratio. Results. The study was terminated after a midway interim analysis because of significantly higher reoperation rate in the X-stop group (33%). The incremental cost for X-stop compared with minimally invasive decompression was [Euro sign]2832 (95% confidence interval: 1886–3778), whereas the incremental health gain was 0.11 quality-adjusted life-year (95% confidence interval: −0.01 to 0.23). Based on the incremental cost and effect, the incremental cost-effectiveness ratio was [Euro sign]25, 700. Conclusion. The majority of the bootstrap samples displayed in the northeast corner of the cost-effectiveness plane, giving a 50% likelihood that X-stop is cost-effective at the extra cost of [Euro sign]25, 700 (incremental cost-effectiveness ratio) for a quality-adjusted life-year. The significantly higher cost of X-stop is mainly due to implant cost and the significantly higher reoperation rate. Level of Evidence: 2